Molecular-genetic mechanisms underlying fruit and seed coloration in plants - V. F. Adzhieva; O. G. Babak; O. Y. Shoeva; A. V. Kilchevsky; E. K. Khlestkina (Вавиловский журнал генетики и селекции, 2015)
Diverse patterns of plant fruit and seed coloration are determined by the presence of two main types of pigment, carotenoids (red, orange and yellow color) and anthocyanins (purple, blue, red). Thеy belong to two groups of secondary metabolites, isoprenoids and flavonoids. Interest towards the genetic mechanisms that control coloration in plants has recently increased due to the antioxidant and antimicrobial properties of some pigments and their colorless precursors consumed with plant-derived food. The genes encoding enzymes involved in step-bystep conversion of initial organic molecules to final pigmented compounds are referred to as structural genes, while regulatory genes are responsible for activation of the expression of structural genes and control the synthesis of pigments at certain times and in proper tissue. The data in plant genetics accumulated to date show that the inter- and intraspecies phenotypic diversity in coloration is mainly related with regulatory genes. Previously developed rich gene collections and precise genetic models for coloration traits in dicots and monocots as well as the rapid development of molecular genetic methods for studying plants allowed for studying genetic regulation of pigment synthesis at a molecular level. The peculiarities of the regulation of carotenoid biosynthesis are exemplified with Solanaceae fruits. The genetic mechanisms underlying the synthesis of various flavonoid pigments are exemplified with a study of seed color in Poaceae plants. In summary, prospects for the practical use of regulatory genes that control pigment synthesis are discussed and examples of their practical use in vegetable and cereal crop breeding are given.